TRIM69 inhibits vesicular stomatitis Indiana virus - Rihn, Suzannah; Stanifer, Megan (Journal of virology, 2019)
Vesicular stomatitis Indiana virus (VSIV), formerly known as vesicular stomatitis virus (VSV) Indiana (VSVIND), is a model virus that is exceptionally sensitive to the inhibitory action of interferons (IFNs). Interferons induce an antiviral state by stimulating the expression of hundreds of interferon-stimulated genes (ISGs). These ISGs can constrain viral replication, limit tissue tropism, reduce pathogenicity, and inhibit viral transmission. Since VSIV is used as a backbone for multiple oncolytic and vaccine strategies, understanding how ISGs restrict VSIV not only helps in understanding VSIV-induced pathogenesis but also helps us evaluate and understand the safety and efficacy of VSIV-based therapies. Thus, there is a need to identify and characterize the ISGs that possess anti-VSIV activity. Using arrayed ISG expression screening, we identified TRIM69 as an ISG that potently inhibits VSIV. This inhibition was highly specific as multiple viruses, including influenza A virus, HIV-1, Rift Valley fever virus, and dengue virus, were unaffected by TRIM69. Indeed, just one amino acid substitution in VSIV can govern sensitivity/resistance to TRIM69. Furthermore, TRIM69 is highly divergent in human populations and exhibits signatures of positive selection that are consistent with this gene playing a key role in antiviral immunity. We propose that TRIM69 is an IFN-induced inhibitor of VSIV and speculate that TRIM69 could be important in limiting VSIV pathogenesis and might influence the specificity and/or efficacy of vesiculovirus-based therapies. - IMPORTANCE Vesicular stomatitis Indiana virus (VSIV) is a veterinary pathogen that is also used as a backbone for many oncolytic and vaccine strategies. In natural and therapeutic settings, viral infections like VSIV are sensed by the host, and as a result the host cells make proteins that can protect them from viruses. In the case of VSIV, these antiviral proteins constrain viral replication and protect most healthy tissues from virus infection. In order to understand how VSIV causes disease and how healthy tissues are protected from VSIV-based therapies, it is crucial that we identify the proteins that inhibit VSIV. Here, we show that TRIM69 is an antiviral defense that can potently and specifically block VSIV infection.